Implementasi dan Pelatihan Penggunaan Sistem Informasi Persediaan Obat Berbasis Web pada Apotek Sekawan Semarang: Deployment and Training on the Utilization of a Web-Based Pharmaceutical Inventory Information System at Sekawan Pharmacy, Semarang - Khoiriyah, Nuzulia; Subroto, Imam Much. Ibnu; Nurhidayah, Eva (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Sekawan Pharmacy, located at Jl. Tlogosari Raya II/47 H, Tlogosari Kulon, Pedurungan District, Semarang City, Central Java, has not yet implemented a structured drug procurement plan based on a forward-looking drug needs analysis. Drug data recording is still conducted manually, with some records managed using Microsoft Excel. However, the use of Microsoft Excel for drug data recording is limited, as it only includes basic information such as drug name, purchase price, drug type, unit, and expiration date. Manual data recording presents several challenges, including errors in checking drug availability and inventory, as well as inaccuracies in monitoring stock fluctuations. These issues often result in discrepancies in final stock calculations and stock shortages when needed. A Community Service Program was carried out through the development of a web-based drug inventory information system and training on its usage to address the needs of Sekawan Pharmacy in improving its stock management efficiency. This initiative aims to enhance the pharmacy's ability to meet consumer demands promptly. The implementation process of the information system and training proceeded smoothly. Users were able to operate the system effectively, as it is designed to be easy to understand and use.